Surgical aortic valve replacement in octogenarians: results in patients who could be considered for transcatheter aortic valve implantation. (22nd September 2015) - Baumbach, A; Kesavan, S; Khan, Y; Iqbal, A; Townsend, M; Hutter, J; Turner, M
Abstract : Transcatheter aortic valve implantation (TAVI) is evolving as an alternative to surgical aortic valve replacement (AVR) in octogenarians with symptomatic aortic stenosis who are considered at high risk for surgical mortality and morbidity. Most series of TAVI recipients compare clinical results against surgical risk scores that predict mortality and morbidity. Few data are available for actual surgical results in patients who might now be considered candidates for TAVI. We conducted a retrospective analysis of AVR results in octogenarians in our unit. All data relevant for the current process of selection into the TAVI programme were assessed by review of the patient notes. A subgroup of patients who would formally be considered for TAVI was created and their results were analysed separately. Results: 298 patients aged 80 years or older underwent surgical AVR between 1996 and August 2008. Of those, 140 patients had AVR for aortic stenosis and 133 had AVR and bypass surgery for aortic stenosis and symptomatic coronary disease. Out of these groups, 82 (isolated AVR) and 85 (AVR plus coronary artery bypass grafting) had a logistic Euroscore greater than 10. Conclusions: The scores used to predict surgical mortality overestimate the risk of the operation in octogenarians. However, registry results of TAVI programmes suggest similar results for high-risk patient cohorts. A direct comparison appears justified.